THE EFFECT OF MOTIVATION, WORK ENVIRONMENT AND DISCIPLINE ON EMPLOYEE PRODUCTIVITY AT PT. ABC - Adelia; masruri masruri; Ade Indra Permana (Maneggio, 2025)
This study aims to examine the effect of work motivation, work environment, and work discipline on employee productivity at PT. ABC. The research method used is quantitative with an associative approach. The population in this study were all employees of PT. ABC, with a sample of 80 respondents selected using purposive sampling technique. Data collection was carried out through distributing questionnaires that had been tested for validity and reliability. The research instrument includes independent variables, namely work motivation (X1), work environment (X2), and work discipline (X3), and the dependent variable is employee productivity (Y). Data analysis was conducted using the Structural Equation Modeling (SEM) model based on Partial Least Square (PLS) version 3.2.9. The results showed that work motivation has a positive and significant effect on employee productivity. The work environment also has a positive and significant effect, indicating that good working conditions can increase employee output. Work discipline proved to have the strongest and most significant influence on productivity, indicating the importance of discipline in supporting the achievement of company targets. Simultaneously, the three variables contribute to increasing employee productivity in the company. This study recommends that companies improve motivation programs, create a more conducive work environment, and enforce discipline rules consistently to achieve optimal productivity.